Risk stratification and treatment of pulmonary embolism with intermediate-risk of mortality. Issue 5 (18th September 2022) - Pastré, Jean; Sanchis-Borja, Mateo; Benlounes, Manil
Abstract : Purpose of review: Intermediate-risk pulmonary embolisms (PE) represent a heterogeneous group at the high end of hemodynamically stable patients, characterized by a higher mortality rate. This challenging population gathers many unsolved question regarding its therapeutic management. The purpose of this review is to provide an updated overview of the literature regarding further risk stratification and treatment options in this population. Recent findings: If anticoagulation represents the undisputed first line of treatment, some patients especially in the intermediate-high risk subgroup may necessitate or could benefit from therapeutic escalation with reperfusion therapies. This includes systemic thrombolysis (ST) or catheter-directed therapies (CDT). ST, despite its high efficacy, is not recommended in this population because of prohibitive bleeding complications. Therefore, reduced-dose ST appears to be a promising option and is actually under evaluation. CDT are percutaneous reperfusion techniques developed to acutely decrease pulmonary vascular obstruction with lower-dose or no thrombolytic agents and, thus, potentially improved safety compared to ST. Summary: Great progress has been made in the recent years providing a wide range of therapeutic options. Optimal selection of patients who could benefit from these treatments is the key and is based on clinical, biological and radiological parameters evaluating right ventricle function and allowing accurate risk stratification. Pulmonary Embolism Response Team represents an efficient modality for therapeutic management especially in the intermediate-high risk subgroup.